The Urgency of Criminal Regulations Against Online Gambling Players - Triska Kristanti, Verina; Fatmawati Octarina, Nynda (International Journal of Social Science, Education, Communication and Economics, 2024)
The criminal act of gambling in Indonesia is regulated in the Criminal Code (KUHP) Article 303 and the Information and Electronic Transactions Law (UU ITE) Article 27 paragraph (2) which can generally be applied to online gambling players even if the person concerned does not gambling as a livelihood, but in practice law enforcement is more targeted at online gambling organizers and is not yet optimal for ensnaring online gambling players at the individual level so that weak law enforcement against online gambling players has the potential to give rise to legal uncertainty, so this research is a type of normative legal research or literature research that carried out by examining theories, concepts, legal principles and statutory regulations related to the urgency of criminal regulation of online gambling players in fulfilling the principle of legal certainty through a statutory approach and a conceptual approach with primary legal material sources, the Criminal Code and the Law. ITE as well as secondary legal materials in the form of books, scientific journals, articles, literature related to this topic which are collected through literature studies and analyzed deductively so that they can provide prescriptions for criminal regulations for online gambling players who must guarantee the law. certainty in order to protect the public from the increasing dangers of widespread online gambling.